ASSISTANCE IN MAKING ONLINE PROMOTIONAL MEDIA AND EFFORTS TO IMPROVE SERVICE QUALITY AT CAR WASH BUSINESS IN TANGERANG - Arifin Djakasaputra; Sanny Ekawati; Rosmita Rasyid (Journal of Community Service and Engagement, 2021)
This PKM activity aims to help newly established entrepreneurs to promote their business online. In addition, they provided training to business owners and employees to improve services according to what consumers want. The long-term goal is to increase business partners to be better known, interested in the community and increase sales through better services. This study was conducted because of the partners' main problem. Namely, the limited working capital, so online promotion is still impossible. Considering the condition of partners who have only started their business for one year, efforts need to be made to remind partners to pay attention to their services' quality so that customers who come can become partners' regular customers. The development of this Website will be carried out by referring to the 7Cs framework, namely: context, content, community, customization, communication, connection, commerce, thereby producing an interactive form of promotional media. The method of implementing the activity is providing knowledge about online promotion, training, socialization about the quality of services and assistance in online media creation and maintenance. The results of this PKM activity are in the form of making a website and exposure material about the quality of employee services. Thus, it is hoped that this business can be better known to the broader community, and business owners can retain consumers to become regular partners. In the end, we will get the sales as desired.